2011
DOI: 10.1021/jo201179p
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of 2,3-Diamino-2,3-dideoxy-β-d-mannopyranosyl Uronates

Abstract: With the aim to find an efficient synthetic procedure for the construction of 2,3-diamino-2,3-dideoxy-β-D-mannuronic acids, we evaluated three mannosyl donors: (S)-phenyl 4,6-di-O-acetyl-2,3-diazido mannopyranoside, (S)-phenyl 2,3-diazido-4,6-O-benzylidene mannopyranoside, and (S)-phenyl 2,3-diazido mannopyranosyl methyl uronate. The first two mannosylating agents are rather unselective or slightly α-selective in their condensation with three different acceptors. The mannuronic acid donor on the other hand rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 55 publications
1
44
0
Order By: Relevance
“…10 The oxidation of the primary alcohol by 2,2,6,6-tetramethyl-1-piperidinyloxy free radical (TEMPO) and (diacetoxyiodo)benzene (BAIB) generated the uronic acid 3 . 6a Esterification of the carboxylic acid with methyl iodide (MeI)/K 2 CO 3 gave the fully protected methyl mannuronate 4 . 6a N -Bromosuccinimide (NBS) removed the anomeric thiophenyl group to produce hemiacetal 5 with a free anomeric hydroxyl group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The oxidation of the primary alcohol by 2,2,6,6-tetramethyl-1-piperidinyloxy free radical (TEMPO) and (diacetoxyiodo)benzene (BAIB) generated the uronic acid 3 . 6a Esterification of the carboxylic acid with methyl iodide (MeI)/K 2 CO 3 gave the fully protected methyl mannuronate 4 . 6a N -Bromosuccinimide (NBS) removed the anomeric thiophenyl group to produce hemiacetal 5 with a free anomeric hydroxyl group.…”
Section: Resultsmentioning
confidence: 99%
“…4a,b Previously we have demonstrated the automated solution-phase synthesis 5a of a β -1,4-mannan hexamer 5b and an insect N -glycan structure 5c by applying a β -directing C-5 carboxylate (mannuronate) methodology inspired in part by van der Marel and coworkers. 6 Unlike the more common 4,6- O -benzylidene-acetal technique for β -mannoside formation invented by Crich and coworkers 7 , the mannuronate glycosyl donor allows a more straightforward deprotection strategy, higher glycosylation temperature, and robustness against acidic conditions. 6 However, the generality of this approach to making other β -mannoside oligomers such as the β -1,2-, 1,3- and 1,6-mannans was unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). [31] Because the glycosylation behavior of 2,3-diazido mannosylating agents has been rarely investigated, [32] we also examined S-phenyl 2,3-diazido-4,6-Obenzylidene mannopyranoside 54 and S-phenyl 4,6-di-O-acetyl-2,3-diazido mannopyranoside 55 as potential donors for the construction of the β-2,3-diaminomannosyl bond. Variable temperature NMR experiments revealed that all three donors were rapidly transformed into their α-anomeric triflates upon treatment with Ph 2 SO/Tf 2 O at -80 • C, as depicted in Figure 3.…”
Section: The Diazidomannuronic Acid Casementioning
confidence: 99%
“…The β-selectivity of the diazidomannuronate donor was exploited in the assembly of a tetrasaccharide 73, [31] representing the [→4)-β-D-ManpA2,3(NAc) 2 -(1→6)-α-DGlcp-(1→4)-β-D-ManpA2,3(NAc) 2 -(1→3)-α-D-GlcpNAc-(1→] repeating unit of the secondary cell wall polysaccharide of Bacillus stearothermophilus (Sch. 5).…”
Section: The Diazidomannuronic Acid Casementioning
confidence: 99%